1999
DOI: 10.1016/s0009-9236(99)80337-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety and pharmacokinetics of alfuzosin 10 mg once daily formulation comparatively to standard formulation (2.5 mg tid) in elderly subjects

Abstract: Clinical Pharmacology & Therapeutics (1999) 65, 202–202; doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The properties of once-daily formulation of alfuzosin were studied in an elderly population without finding any pharmacokinetic difference in 16 healthy volunteers between 66 and 78 years. 24 Despite 35% greater concentration of alfuzosin in patients aged ⩾75 years, 22 clinical trials showed no overall differences in safety or effectiveness between subjects ⩾65 years, ⩾75 years and younger men. 22…”
Section: Alfuzosin: Pharmacology and Pharmacodynamicsmentioning
confidence: 98%
See 1 more Smart Citation
“…The properties of once-daily formulation of alfuzosin were studied in an elderly population without finding any pharmacokinetic difference in 16 healthy volunteers between 66 and 78 years. 24 Despite 35% greater concentration of alfuzosin in patients aged ⩾75 years, 22 clinical trials showed no overall differences in safety or effectiveness between subjects ⩾65 years, ⩾75 years and younger men. 22…”
Section: Alfuzosin: Pharmacology and Pharmacodynamicsmentioning
confidence: 98%
“…23 The properties of once-daily formulation of alfuzosin were studied in an elderly population without finding any pharmacokinetic difference in 16 healthy volunteers between 66 and 78 years. 24 Despite 35% greater concentration of alfuzosin in patients aged ⩾75 years, 22 clinical trials showed no overall differences in safety or effectiveness between subjects ⩾65 years, ⩾75 years and younger men. 22 As regards the pharmacodynamic profile of alfuzosin in special populations, the presence of chronic heart failure has not been found to significantly affect the pharmacokinetics of 10 mg daily alfuzosin.…”
Section: Alfuzosin: Pharmacology and Pharmacodynamicsmentioning
confidence: 98%